ASISTENSI RELAWAN PAJAK, KESADARAN, DAN KOMPLEKSITAS PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Apip; Hery Laksito (Jurnal Ekonomi Dan Bisnis, 2026)
This study examines the effect of tax volunteer assistance, taxpayer awareness, and tax complexity on individual taxpayer compliance at the Small Tax Office of West Semarang. Using a quantitative approach, the population comprised 128,347 registered taxpayers. A sample of 100 respondents was selected using the Slovin formula and simple random sampling. Primary data were collected via a five point Likert scale questionnaire distributed directly from 27 February to 19 March 2024. Data analysis utilized multiple linear regression after satisfying validity, reliability, and classical assumption tests. Results indicate that taxpayer awareness positively and significantly affects compliance. Conversely, tax volunteer assistance and tax complexity have no significant effect. Simultaneously, all independent variables significantly affect compliance with an adjusted R square of 0.549, explaining 54.9 percent of the variance. These findings imply that internal awareness plays a more decisive role than external assistance programs or perceived regulatory complexity in shaping compliance behavior